Cross-presentation: dendritic cells and macrophages bite off more than they can chew! - Brode, Sven (Blackwell Science Inc, 2004)
As immunologists, our knowledge of the molecular mechanisms which underlie the presentation of antigens derived from extracellular or ‘exogenous’ sources to CD8 cytotoxic lymphocytes (CTL) has been limited. This process, termed ‘cross-presentation’, has been linked to the elicitation of protective CTL responses against tumours and may be extremely important in generating immune responses against clinically relevant pathogens that do not infect tissues of haemopoietic origin. It is now known that cross-presentation of exogenous antigens on major histocompatibility complex (MHC) class I occurs through several distinct cellular pathways. In this review we outline and discuss some recent advances in our understanding of these pathways.